Tanreqing Injection Attenuates Macrophage Activation and the Inflammatory Response via the lncRNA-SNHG1/HMGB1 Axis in Lipopolysaccharide-Induced Acute Lung Injury - Hu, Chunling; Li, Junlu; Tan, Yingshuai; Liu, Yang; Bai, Chen; Gao, Jing; Zhao, Shilong; Yao, Mengying; Lu, Xiaoxiao; Qiu, Lingxiao; Xing, Lihua (Frontiers in Immunology, 2022)
The etiology of acute lung injury (ALI) is not clear, and the treatment of ALI presents a great challenge. This study aimed to investigate the pathogenesis and potential therapeutic targets of ALI and to define the target gene of Tanreqing (TRQ), which is a traditional Chinese medicine formula composed of five medicines, scutellaria baicalensis, bear bile powder, goat horn powder, honeysuckle and forsythia. Macrophage activation plays a critical role in many pathophysiological processes, such as inflammation. Although the regulation of macrophage activation has been extensively investigated, there is little knowledge of the role of long noncoding RNAs (lncRNAs) in this process. In this study, we found that lncRNA-SNHG1 expression is distinctly regulated in differently activated macrophages in that it is upregulated in LPS. LncRNA-SNHG1 knockdown attenuates LPS-induced M1 macrophage activation. The SNHG1 promoter was bound by NF-κB subunit p65, indicative of SNHG1 being a direct transcriptional target of LPS-induced NF-κB activation. SNHG1 acts as a proinflammatory driver that leads to the production of inflammatory cytokines and the activation of macrophages and cytokine storms by physically interacting with high-mobility group box 1 (HMGB1) in ALI. TRQ inhibited NF-κB signaling activation and binding of NF-κB to the SNHG1 promoter. In conclusion, this study defined TRQ target genes, which can be further elucidated as mechanism(s) of TRQ action, and provides insight into the molecular pathogenesis of ALI. The lncRNA-SNHG1/HMGB1 axis is an ideal therapeutic for ALI treatment.